1989
DOI: 10.1111/j.1439-0450.1989.tb00582.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Identity of Sarcocystis Cysts in Cattle in Belgium

Abstract: Muscle tissue from the oesophagus, diaphragm and heart of 100 cattle slaughtered in Belgium was examined for Sarcocystis infection by microscopic examination of tissue and artificial digestion. Intact sarcocysts or cystozoietes were recovered from 97% of the cattle examined. There was a difference in sensitivity between the method (digestion or histology) used and the muscle processed. The digestion of the oesophagus muscle resulted in the highest number of positive animals whereas the heart muscles contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
4
11
2
1
Order By: Relevance
“…observed in both farms is in agreement with other studies from several countries that indicate up to 100% prevalence, especially for S. cruzi (Böttner et al 1987;Dubey et al 1989;Latif et al 1999;Van Knapen et al 1987;Vercruysse et al 1989). Neospora caninum seroprevalence may vary widely depending on diagnostic technique and cutoff titer used (Dubey et al 2007); however, in the present study seroprevalence in cows and calves was similar to that reported previously in Argentina (Moré et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…observed in both farms is in agreement with other studies from several countries that indicate up to 100% prevalence, especially for S. cruzi (Böttner et al 1987;Dubey et al 1989;Latif et al 1999;Van Knapen et al 1987;Vercruysse et al 1989). Neospora caninum seroprevalence may vary widely depending on diagnostic technique and cutoff titer used (Dubey et al 2007); however, in the present study seroprevalence in cows and calves was similar to that reported previously in Argentina (Moré et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…After an initial survey on 203 cattle, the oesophagus was chosen as the most suitable organ for detecting Sarcocystis infection. This was in line with previous studies on bovine sarcocystosis [8,9].…”
Section: Methodssupporting
confidence: 93%
“…infection of 52 % which is lower than that reported from other countries. Using similar techniques, Hinaidy and co-workers [12] reported a prevalence of 87 % in Austria, Vercruysse and colleagues [9] found 97 % of cattle infected in Belgium, Boch and Erber [13] reported a prevalence of 99% in the Federal Republic of Germany and Bottner and co-workers [8] reported a prevalence of 97 % in New Zealand. The factors thought most likely to be responsible for the low prevalence in WA include the low densities of both the definitive and the intermediate host and the relative aridity of much of the region.…”
Section: Discussionmentioning
confidence: 99%
“…References relating to the spread of parasites in European cattle are scarce and often rather vague about Sarcocystis typing, which is sometimes conducted only by assessment of cyst wall thickness. Since the cysts of S. cruzi are thin-walled, they are easily identifiable by light microscopy; however, the same cannot be said for S. hominis and S. hirsuta, both of which have thick-walled cysts that make them indistinguishable from each other (Mehlhorn and Heydorn 1978;Vercruysse et al 1989).…”
Section: Introductionmentioning
confidence: 94%